2021
DOI: 10.3390/cancers13164233
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment in Breast Cancer—Updates on Therapeutic Implications and Pathologic Assessment

Abstract: The tumor microenvironment (TME) in breast cancer comprises local factors, cancer cells, immune cells and stromal cells of the local and distant tissues. The interaction between cancer cells and their microenvironment plays important roles in tumor proliferation, propagation and response to therapies. There is increasing research in exploring and manipulating the non-cancerous components of the TME for breast cancer treatment. As the TME is now increasingly recognized as a treatment target, its pathologic asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 216 publications
(258 reference statements)
2
89
0
1
Order By: Relevance
“…It is also important to consider that other factors may also contribute to the response to the combined inhibition of FAK and mTORC1. These include the potential of hypoxia, other cell types (i.e., adipocytes and myoepithelial cells), and soluble factors (i.e., matrix remodeling enzymes, cytokines, and growth factors) to modulate the ECM [ 84 ].. Discerning the impact of mTORC1 and FAK inhibition on the complex interplay of these factors and their impact on in vivo tumor growth are warranted to discern the potential mechanisms of synergy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider that other factors may also contribute to the response to the combined inhibition of FAK and mTORC1. These include the potential of hypoxia, other cell types (i.e., adipocytes and myoepithelial cells), and soluble factors (i.e., matrix remodeling enzymes, cytokines, and growth factors) to modulate the ECM [ 84 ].. Discerning the impact of mTORC1 and FAK inhibition on the complex interplay of these factors and their impact on in vivo tumor growth are warranted to discern the potential mechanisms of synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Another important point to consider is the variation in the structure of the tumour microenvironment among different cancers, as it has been shown that tumour microenvironments differ in terms of cell types and the composition of the extracellular matrix [ 75 , 76 , 77 ]. Moreover, crosstalk between MSCs and other cell types in the tumour microenvironment and certain properties of the microenvironment (e.g., pH, O 2 concentration, and ion gradients) importantly affect MSC development and characteristics and the heterogeneity of the population [ 73 , 78 ].…”
Section: The Ambivalent Nature Of Mscs In the Tumour Microenvironmentmentioning
confidence: 99%
“…This is seen though changes to the TME cellular composition, recruiting cells like mesenchymal stem cells, adipose stem cells, dendritic cells and tumour-associated macrophages, all with distinct roles in inflammatory pathways 42 . Latest World Health Organisation (WHO) classification of breast tumours has listed stromal cell response patterns as prognostic factors 43 .…”
Section: The Role Of the Tme In Breast Cancermentioning
confidence: 99%
“…The invasion of tumour-infiltrating lymphocytes was reported as a predictor of survival and response to neoadjuvant treatments, in TNBC and HER2 positive cancer 43 . In comparison, the presence of macrophages was associated with unfavourable prognoses for patient survival 43 .…”
Section: The Role Of the Tme In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation